History of research on glaciation in the White Mountains, New Hampshire (U.S.A.) - Thompson, Woodrow (Géographie physique et Quaternaire, 1999)
AbstractThe glacial geology of the White Mountains in New Hampshire has been the subject of many investigations since the 1840's. A series of controversies evolved during this period. First was the question of what geologic processes were responsible for eroding the bedrock and depositing the cover of surficial sediments. By the 1860's, the concept of glaciation replaced earlier theories invoking floods and icebergs. Research in the late 1800's concerned the relative impact of continental versus local glaciation. Some workers believed that surficial deposits in northern New Hampshire were the product of valley glaciers radiating from the White Mountains, but in the early 1900's continental glaciation was established as the most important process across the region. Debate over the extent and timing of alpine glaciation in the Presidential Range has continued until recent years. The most intensely argued topic has been the manner in which the Late Wisconsinan ice sheet withdrew from the White Mountains: whether by rapid stagnation and downwastage, or by progressive retreat of a still-active ice margin. The stagnation model became popular in the 1930's and was unchallenged until the late 1900's. Following a research hiatus lasting over 40 years, renewed interest in the glacial history of the White Mountains continues to inspire additional work.